Catalytic Role of the Substrate Defines Specificity of Therapeutic l-Asparaginase. Issue 17 (28th August 2015) - Anishkin, Andriy; Vanegas, Juan M.; Rogers, David M.; Lorenzi, Philip L.; Chan, Wai Kin; Purwaha, Preeti; Weinstein, John N.; Sukharev, Sergei; Rempe, Susan B.
Abstract: Type II bacterial l -asparaginases (l -ASP) have played an important therapeutic role in cancer treatment for over four decades, yet their exact reaction mechanism remains elusive. l -ASP from Escherichia coli deamidates asparagine (Asn) and glutamine, with an ~ 10 4 higher specificity ( k cat / K m ) for asparagine despite only one methylene difference in length. Through a sensitive kinetic approach, we quantify competition among the substrates and interpret its clinical role. To understand specificity, we use molecular simulations to characterize enzyme interactions with substrates and a product (aspartate). We present evidence that the aspartate product in the crystal structure of l -ASP exists in an unusual α-COOH protonation state. Consequently, the set of enzyme–product interactions found in the crystal structure, which guided prior mechanistic interpretations, differs from those observed in dynamic simulations of the enzyme with the substrates. Finally, we probe the initial nucleophilic attack with ab initio simulations. The unusual protonation state reappears, suggesting that crystal structures (wild type and a T89V mutant) represent intermediate steps rather than initial binding. Also, a proton transfers spontaneously to Asn, advancing a new hypothesis that the substrate's α-carboxyl serves as a proton acceptor and activates one of the catalytic threonines during l -ASP's nucleophilic attack on the amide carbon. That hypothesis explains for the first time why proximity of the substrate α-COO − group to the carboxamide is absolutely required for catalysis. The substrate's catalytic role is likely the determining factor in enzyme specificity as it constrains the allowed distance between the backbone carboxyl and the amide carbon of any l -ASP substrate. Graphical abstract: Highlights: Deamidation mechanism of l -ASP (a cancer treatment enzyme) remains unknown. Competition kinetics rationalize clinical changes in substrate (Asn/Gln) levels. Product's unusual protonation in l -ASP crystal alters interactions with enzyme. Ligand structure in l -ASP crystals resembles simulated intermediates, not substrates. Substrate accepts nucleophile's proton, limiting substrate amide-to-α-COO − distance.